From Patches to Plaques: A Diagnostic Challenge in a Case of Erythroderma Secondary to Pityriasis Rubra Pilaris - Kamilah, Lian; Rahmat Firdaus Dwi Utama; Shelly Lavenia Sambodo; Muhammad Eko Irawanto (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Erythroderma, a dramatic and potentially life-threatening condition characterized by fiery redness engulfing over 90% of the skin's surface, presents a formidable diagnostic challenge due to its myriad underlying causes. Among these, pityriasis rubra pilaris (PRP), a rare inflammatory skin disorder, stands out with its distinctive features and often perplexing presentation. This case unveils the intricate diagnostic journey of a young man whose erythroderma masked an underlying PRP, further complicated by the subtle interplay of stress. Case presentation: An 18-year-old male presented with a one-month history of alarming erythroderma accompanied by distressing itching, fever, and sleep disturbances. Adding to the complexity, he exhibited characteristic 'nappes claires' – islands of normal skin amidst the erythrodermic sea – a hallmark of PRP. Palmoplantar keratoderma, alopecia areata, and ectropion further painted an intriguing clinical picture. Histopathological examination revealed the telltale 'checkboard' pattern, confirming PRP as the culprit. Notably, the patient's history revealed a compelling link between stress and disease exacerbation, adding a psychosomatic dimension to the case. Systemic corticosteroids and methotrexate, alongside topical emollients, brought about significant clinical improvement, underscoring the importance of early diagnosis and targeted treatment. Conclusion: This case underscores the critical need to consider PRP in the labyrinth of erythroderma diagnoses, particularly when 'nappes claires' and a history of stress are intertwined. By shining a light on the diagnostic subtleties and therapeutic nuances of PRP-associated erythroderma, this report empowers clinicians to navigate the complexities of this rare and challenging condition, ultimately improving patient outcomes and quality of life.